Learning Process During the Month of Ramadan for English Language Education Students at Universitas Muria Kudus - Slamet Utomo (Jurnal Ilmiah Wahana Pendidikan, 2026)
The purpose of this study is to determine the learning process of English language education students at Universitas Muria Kudus during the month of Ramadan. The type of research used is quantitative research using an electronic questionnaire in the form of Google Form. The research respondents were 6th semester students. Based on the research questionnaire, the results obtained were the majority of students felt that the optimal learning process was carried out using the hybrid method, the optimal learning process was carried out in the morning, learning concentration was in the good category and learning enthusiasm was in the enthusiastic category during the learning process during the month of Ramadan.